GRI (Global Reporting Initiative) as a Reporting Standard of Non-Financial Information in the Area of ESG (Environmental, Social, Corporate Governance). The Case of Banks Listed on the Warsaw Stock Exchange - Zabawa, Justyna; Łosiewicz-Dniestrzańska, Ewa (Journal of Finance and Financial Law, 2023)
The purpose of the article. The objectives of the article: 1) identification of currently applicable regulations (in the field of “hard law” and “soft law”) in the area of ESG relating to the banking sector in the period 2015–2023; 2) defining the scope of the implementation of the GRI standard for non-financial reporting in the banking sector on the example of banks listed on the Warsaw Stock Exchange in the period 2017–2022, with particular emphasis on banks from the WIG-ESG index. Methodology. The research methods used include, among others: critical analysis of the literature on the subject, analysis of legal acts and regulations, analysis of non-financial reports of the surveyed banks. Results of the research. The study analyzed issues related to: the standards used in non-financial reporting, participation in the WIG-ESG Index, integration of financial and non-financial data, as well as the evaluation of report names. It has been confirmed that the GRI (Global Reporting Initiative) Standard is currently the dominant standard for reporting of non-financial information in the banking sector. Additionally, more and more banks have integrated non-financial data with financial data. Nine out of ten banks were included in the composition of the WIG-ESG Index.